1976
DOI: 10.1128/iai.13.2.337-344.1976
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a one-hit theory in the immune bactericidal reaction and demonstration of a multi-hit response for hemolysis by streptolysin O and Clostridium perfringens theta-toxin

Abstract: An analytical method was developed for estimating the number of hits necessary to lyse or kill cells in which various concentrations of the cells are treated with a constant amount of the lytic or killing agent in a constant reaction volume. The reaction may be due to a single-component agent or occur by a sequential chain of reactions due to a multi-component agent, even including side, abortive, or counter-reactions. It was clearly shown by this method that immune bactericidal reactions followed a one-hit th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Some traits, for example resistance to penicillin or loss of a growth requirement for uracil, have required up to 6 h for full phenotypic expression (14). Inoue et al (8) have presented evidence to show that the onehit theory of immune hemolysis could be extended to the immune bactericidal reaction. This could explain the unusually long time required for phenotypic expression.…”
Section: Resultsmentioning
confidence: 99%
“…Some traits, for example resistance to penicillin or loss of a growth requirement for uracil, have required up to 6 h for full phenotypic expression (14). Inoue et al (8) have presented evidence to show that the onehit theory of immune hemolysis could be extended to the immune bactericidal reaction. This could explain the unusually long time required for phenotypic expression.…”
Section: Resultsmentioning
confidence: 99%
“…Mayer [17,18] proposed the 'one-hit' theory that suggested a single 'complement hit' could cause lysis of an erythrocyte. This was later supported by Inoue et al who showed that the complement could kill a bacterium by a single hit [19]. Using a reconstitution assay, Mayer and colleagues added partially purified components to antibody-sensitised sheep erythrocytes to unravel the reaction sequence of the classical pathway [20,21].…”
Section: Historymentioning
confidence: 99%
“…The gram-negative cell obviously presents a more complex target for complement attack than the erythrocyte; bacteria have a more complex envelope structure, they can respond rapidly to changes in the environment, and they have a capacity for repair of damaged sites. Nevertheless, Inoue et al (128) developed an analytical method for determination of the number of lesions necessary for killing of E. coli B that involved exposure of increasing concentrations of antibody-sensitized bacteria to a constant amount of complement;…”
Section: Sequence Of Events After Exposure To Serummentioning
confidence: 99%